Relapse to narcotic addiction: The role of methadone in modifying conditioned abstinence symptoms in humans - Mandelzys, Nathan (University of Ottawa (Canada), 1977)
Abstract not available.
Keywords: Psychology, Behavioral.; Health Sciences, Public Health.; Psychology, Physiological.